2020
DOI: 10.1186/s12870-020-02643-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of zinc and IAA alleviate aluminum-induced damage on photosystems via promoting proton motive force and reducing proton gradient in alfalfa

Abstract: Background In acidic soils, aluminum (Al) competing with Zn results in Zn deficiency in plants. Zn is essential for auxin biosynthesis. Zn-mediated alleviation of Al toxicity has been rarely studied, the mechanism of Zn alleviation on Al-induced photoinhibition in photosystems remains unclear. The objective of this study was to investigate the effects of Zn and IAA on photosystems of Al-stressed alfalfa. Alfalfa seedlings with or without apical buds were exposed to 0 or100 μM AlCl3 combined with 0 or 50 μM ZnC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the increase of DIo/RC suggests that Zn-deficiency results in ineffective energy management, which is correlated with the reduced photosynthetic efficiency in leaves of Zn-deprived tomato. Zn functions during photosynthesis when CO 2 is fixed, although chloroplast and photosynthesis can be impaired under deficiency 36,37 . Several cellular dysfunctions and damages related to plant abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increase of DIo/RC suggests that Zn-deficiency results in ineffective energy management, which is correlated with the reduced photosynthetic efficiency in leaves of Zn-deprived tomato. Zn functions during photosynthesis when CO 2 is fixed, although chloroplast and photosynthesis can be impaired under deficiency 36,37 . Several cellular dysfunctions and damages related to plant abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Zn can also improve the resistance of plants to abiotic stress by scavenging reactive oxygen species. Studies have shown that Zn plays important roles under drought, heavy metal, salinity, and UV stresses Su et al 2020;Tufail et al 2018). However, the effect of Zn on rice resistance to low temperature is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn), one of the essential micronutrients for plant growth and development, plays a fundamental role in several critical cellular functions, such as protein metabolism, gene expression, structural and functional integrity of the biomembranes, and photosynthetic carbon metabolism (Cakmak 2000;Cakmak et al 2010a;Marschner 1995). Under abiotic stress conditions, Zn acts as the metal component of copper/zinc-superoxide dismutase (SOD) and can scavenge O 2 − • to control reactive oxygen species (ROS) production, thus resulting in less damage to cell membranes and enhanced plant stress tolerance (Rehman et al 2012;Su et al 2020). The absorption of Zn by plants is a process of thermodynamic passive transmembrane absorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations